Psychogenic Polydipsia Complicated to Hyponatremia Induced Seizure in Schizophrenia: A Case Report from Nepal - Sharma, Pawan; Shah, Bigya; Sangroula, Modnath; Jirel, Richan (Case Reports in Psychiatry, 2019)
Psychogenic polydipsia is one of the common cooccurrences with Schizophrenia and if not addressed can lead to fatal consequences. There are some evidences for pharmacological management of this condition but nonpharmacological management starting from psycho-education to behavioural modification therapy involving family members can be a very effective strategy. We report a case from Nepal where psychogenic polydipsia was complicated to hyponatremia and lead to seizure episodes. We emphasize on asking a routine question about polydipsia in every patient of Schizophrenia in clinics.